Kierkegaard and Issues in Contemporary Ethics - Fox-Muraton, Mélissa (Kierkegaard Studies. Monograph Ser., 2020)
While Kierkegaard's philosophy focuses on concrete human existence, his thought has rarely been challenged regarding concrete and contemporary moral issues. This volume offers an overview of contemporary ethical issues from a Kierkegaardian perspective, deliberately taking him out of the sphere of Theology and Christian Ethics, and examining the ways in which his works can provide fruitful insight into questions which Kierkegaard certainly never himself envisaged, such as accepting refugees into our communities, understanding how we relate to social media, issues of identity with regard to bioengineering or transgender identity, or problems of interreligious dialogue. The contributions in this volume, by international scholars, seek to address both the challenges and insights of Kierkegaard's existential ethics for our contemporary societies, and its relation to topics of current interest in the field of moral philosophy. The volume is organized into three major sections: the first focusing on the relation between ethics and religion, a topic of primary importance with regard to the development of religious foundationalism and the challenges of dealing with diverse belief systems within our communities; the second on our understandings of ourselves and our relations to others with regard to issues of media and community; and the third targeting more specifically questions of identity, and the ways in which the developments of modern science impact identity construction. This work offers new paths for critically engaging with the moral issues of our times from an existential perspective.